Analisis keterampilan berpikir kritis pada Kompetensi Dasar Kurikulum 2013 Mata Pelajaran Fisika SMA Analisis keterampilan berpikir kritis pada Kompetensi Dasar Kurikulum 2013 Mata Pelajaran Fisika SMA - Khaeruddin Khaeruddin; Bunga Dara Amin; Jasruddin Jasruddin (Seminar Nasional LP2M UNM, 2019)
The low level of critical thinking skills of students, namely the average value of students doing interpretation, analysis, and inference in a row of 1.53, 1.15, and 1.52. Though the demands of the curriculum, both the 2006 and 2013 curriculum explicitly found keywords in core competencies and basic competencies such as scientific behavior (including curiosity, objectivity, honesty, thoroughness, meticulous, diligent, careful, responsible, open, critical, creative, innovative and caring for the environment), conducting experiments and discussing, analyzing, presenting data and graphics. This means that the Indonesian Curriculum explicitly states that critical thinking skills as future competencies must be taught to students to answer the challenges of globalization and be able to adapt to change and respond to the demands of the 21st century. Therefore, the purpose of this study is to describe indicators of critical thinking skills in the basic competencies of the 2013 Curriculum for High School Physics Subjects